ANALISIS MAKNA KANYOUKU YANG BERKAITAN DENGAN WARNA : KAJIAN LINGUISTIK KOGNITIF - Sekarsari, Widi (2016)
Makna kanyouku atau idiom penting untuk dipahami pembelajar bahasa Jepang, namun penelitian mengenai kanyouku yang khusus berkaitan dengan warna masih terbatas. Penelitian ini bertujuan untuk mengetahui makna leksikal, makna idiomatikal dan hubungan antara makna leksikal dan makna idiomatikal pada kanyouku yang berkaitan dengan warna. Selain itu, juga untuk mengetahui ciri khas makna warna pada kanyouku. Objek penelitian dibatasi pada 18 kanyouku yang menggunakan warna akai, aoi, kiiroi, kuroi, shiroi, dan kokubyaku atau shirokuro. Melalui penelitian dengan menggunakan teori linguistik kognitif ini diperoleh (1) makna leksikal warna dalam kanyouku diartikan sesuai dengan makna asli warna berdasarkan referensi kamus. Makna idiomatikal warna merupakan makna khusus yang muncul dan berbeda dari makna leksikal; (2) terdapat hubungan antara makna leksikal dan makna idiomatikal secara metafora 12 kanyouku, dan metonimi 6 kanyouku; (3) Ciri khas makna warna dalam kanyouku yaitu, merah (peringatan agar berhati-hati), biru (pengganti warna hijau, belum matang dan kurang berpengalaman), kuning (peringatan keselamatan agar berhati-hati, usia muda dan kurang berpengalaman), hitam (tindakan yang jahat, penanda kehidupan), putih (warna yang bersih), hitam putih (perumpamaan benar atau salah dan memperjelas sesuatu). Kata-kata kunci : linguistik kognitif, makna kanyouku, metafora, metonimi Kanyouku or idiom meaning is important to be understood by Japanese language learner, but research about kanyouku which especially related to the color is still limited. The purpose of this research is to know the lexical meaning, the idiomatical meaning, and connection between lexical meaning and idiomatical meaning in kanyouku that related to the color. In addition, it is also to determine the typical meaning of color in kanyouku. The object of the research is limited to 18 kanyouku that using red, blue, yellow, black, white, also black and white colors. Using the theory of cognitive linguistics, this research reveals (1) the lexical meaning of color in kanyouku are defined according to the original meaning of color based on the dictionary reference. The idiomatical meaning of color is a particular meaning that appears to be different than the lexical meaning; (2) there are some connection between lexical meaning and idiomatical meaning. There are 12 meanings metaphorically and 6 meaning metonimycally; (3) Characteristic meaning of color in kanyouku is, red (a warning to being carefull), blue (a substitute for green color, immature and lack of experience), yellow (safety warning to be carefull, young age and lack of experience), black (evil action, sign of life), white (clear color), black and white (parable of right and wrong and make sure of something). Keywords: cognitive linguistics, idiom meaning, metaphor, metonymy